2015
DOI: 10.25100/sye.v0i29.3922
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdad de oportunidades educativas en la población de 15 a 29 años en Brasil y Colombia según autoclasificación étnico-racial

Abstract: El artículo valora los efectos de la condición étnico-racial en el logro educativo en Brasil y Colombia. Se estimaron modelos logísticos ordenados generalizados para el logro edu­cativo. Los resultados mostraron que para la población afrodescendiente en Brasil y Co­lombia es menos probable alcanzar un nivel educativo más alto que para la población no afrodescendiente, pero con un efecto más fuerte y significativo en el caso de Colombia. Esto sugiere la presencia de discriminación premercado en ambos países, y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…In Latin America, studies have investigated educational attainment as a mechanism to document social stratification that exists between racial groups and among groups of varying phenotypes (Paschel & Sawyer, 2008; Russell‐Cole, Wilson, & Hall, 2013; Wade, 1995). These studies indicate that Latin American people of European descent predominantly occupy the highest socioeconomic positions, whereas populations of African and Indigenous descent predominantly occupy positions of low socioeconomic status (Marteleto, 2012; Telles, 2014; Viáfara López & Serna Alvarado, 2015). Although empirical research examining how systems of oppression affect Black youth is often limited to the study of race in the United States, it is equally important to address the racial realities of Black and Brown youth residing in Latin America.…”
Section: Historical Underpinnings Of Racism and Multiculturalism In B...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Latin America, studies have investigated educational attainment as a mechanism to document social stratification that exists between racial groups and among groups of varying phenotypes (Paschel & Sawyer, 2008; Russell‐Cole, Wilson, & Hall, 2013; Wade, 1995). These studies indicate that Latin American people of European descent predominantly occupy the highest socioeconomic positions, whereas populations of African and Indigenous descent predominantly occupy positions of low socioeconomic status (Marteleto, 2012; Telles, 2014; Viáfara López & Serna Alvarado, 2015). Although empirical research examining how systems of oppression affect Black youth is often limited to the study of race in the United States, it is equally important to address the racial realities of Black and Brown youth residing in Latin America.…”
Section: Historical Underpinnings Of Racism and Multiculturalism In B...mentioning
confidence: 99%
“…Marteleto (2012) found that 77.8% of Black Brazilian adolescents transitioned to secondary school compared to 89% of Whites. Viáfara López and Serna Alvarado (2015) found that 6.5% of Brazilians who identified as negro (Black) and 6.1% of those who identified as pardo (Brown) obtained a college degree compared to 16.8% of those who identified as branco (White). For the Colombian sample, 9.7% of those who identified as Black had a college degree or less compared to 27.4% of those who did not identify as Black.…”
Section: Historical Underpinnings Of Racism and Multiculturalism In B...mentioning
confidence: 99%
“…26 Para ejemplificar esto, véanse: Informe de masacres en Colombia durante el 2020-2021, realizado por el Instituto de Estudios para el Desarrollo y la Paz (InDEpAz), disponible en http://www.indepaz.org.co/informe-de-masacres-en-colombia-durante-el-2020/; Gobernador de Nariño denuncia ´masacre de seis jóvenes en Tumaco, disponible en https://www.eltiempo.com/colombia/otras-ciudades/masacre-deseis-jovenes-en-tumaco-narino-denuncia-el-gobernador-532086; Masacre en Tumaco: cinco personas fueron asesinadas, disponible en https://www.elespectador.com/ noticias/nacional/masacre-en-tumaco-cinco-personas-fueron-asesinadas-articulo-916332/; Especial -Tumaco llora una masacre "en tiempos de paz", disponible en https://www.contagioradio.com/tumaco-llora-una-masacre-en-tiempos-de-paz/ 27 Asumimos la etno-diferencialidad como la categoría que analiza la diferencia étnica y cultural de los individuos bajo un principio de autoidentificación en alguna de las categorías pensadas por el Estado. Esta etno-diferencia es heredera de los estudios que profundizan en la configuración étnico-racial de la sociedad, con lo cual se analizan los grupos humanos y las igualdades/desigualdades que pueden experimentar (Viáfara y Serna, 2015). 28 En Colombia las comunidades autoidentificadas como afrocolombianas, negras, raizales y palenqueras pueden resumir su presencia demográfica en dos zonas específicas: la zona Atlántica y la zona Pacífica.…”
Section: Covid-19 En El Border Tumaqueño Entre La Guerra Y La Sobrevivenciaunclassified
“…En el mismo sentido, Viáfara y Serna (2015), en un estudio comparativo de la población afrodescendiente de Brasil y Colombia, afirman que es menos probable alcanzar un nivel educativo más alto para la población afrodescendiente que para la población no afrodescendiente; situación que se presenta en mayor medida para Colombia con referencia a lo que sucede en Brasil. En este estudio, se argumenta que, pese a que estos países cuentan con políticas de acción afirmativa por condición étnico-racial, sigue corroborándose la presencia de un círculo vicioso de desventajas acumulativas para la población afrodescendiente, que opera como desigualdad de oportunidades en el acceso a mayores niveles educativos y en la inserción al mercado laboral.…”
Section: Introductionunclassified